Model Pencegahan Kekerasan Berbasis Gender melalui Komunikasi Dakwah dan Komunitas: Studi Konseptual di Aceh - Anita Anita (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
: Gender-based violence (GBV) remains a serious issue in Aceh, with high prevalence in both domestic and public spheres. This phenomenon is rooted in structural gender inequality, patriarchal norms, and limited public awareness of justice and equality values. This study aims to formulate a conceptual model for GBV prevention through da’wah communication and community engagement, contextualized within Acehnese socio-cultural and religious norms. Through literature analysis, empirical data, and integration of da’wah communication theory with social change theory, the study finds that da’wah communication plays a dual role: as a medium of awareness-building that internalizes Islamic values (rahmatan lil ‘alamin, equality, and anti-violence) and as a means of social transformation that shifts community paradigms and behaviors. The proposed model emphasizes four key factors: gender-just da’wah content, contextual delivery methods, the credibility of da’i as moral exemplars, and sensitivity to local socio-cultural values. Community involvement is crucial in strengthening social solidarity, providing safe spaces, and fostering collective awareness to reject GBV. The study recommends strengthening the capacity of da’i, developing gender-sensitive da’wah materials, enhancing multi-stakeholder collaboration, and utilizing digital media to broaden outreach. Thus, this conceptual model can serve as a strategic reference for local government, religious institutions, and community organizations to build a just, safe, and gender-based violence–free social environment.